Proses Bisnis dan Aspek Perpajakan Jasa Penunjang Minyak dan Gas Bumi untuk Kegiatan Usaha Jasa Konstruksi (Content Analysis dan Hermeneutic Analysis) - Deddy Arief Setiawan (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Revenue of Oil and Gas Income Tax increased by an average of 8.1 percent per year in the period 2006-2010. Oil and Gas Income Tax was produced by the oil and gas industry from upstream activities. The activity is a business activity that is high-risk exploration and production (exploitation). The success of these businesses should be supported by the supporting services of oil and gas. One of these supporting services is construction activity. The focus of this research is the business processes and taxation aspect for supporting services of oil and gas in construction activities. Based on this research focus, the discussion of this research consists of: 1). business process for supporting services of oil and gas in construction activities; and 2). taxation aspects for supporting services of the oil and gas in construction activities. The research methodology these was used a qualitative research approach with data analysis techniques of content analysis and hermeneutic Analyisis. Through content analysis and analyisis hermeneutic understanding of the laws and applicable these laws (law of oil and gas, law of construction services and law of taxation) can be done through a text interpretative with systematic and structured, so that can be generated explanation of business processes and taxation aspects for supporting services of the oil and gas in construction activities. Further data collection is done through field research and case study of taxation aspects for supporting services for oil and gas in construction activities. Business process for supporting services of the oil and gas in construction activity begins with an explanation of the construction services activity on law of construction services. Then proceed with the explanation of the construction services activities according to the law of oil and gas. The activity is one of supporting activities of oil and gas that the implementation is done in accordance with the law of construction services. The conclusion is business process for supporting services of the oil and gas in construction activities with the law of construction service and the law of oil and gas, are the same. However, that should be of particular concern is the Registered Certificate (SKT) from the Director of Engineering and Environmental for Oil and Gas. Taxation aspects for supporting services of the oil and gas in construction activities based on the law of income tax relating to the taxation of construction services that are similar to the taxation aspects for other than the supporting services of oil and gas. The conclusion is that the taxation aspects covering Income Tax Article 4 paragraph (2) shall be final and Income Tax Article 26 paragraph (4) for a Permanent Establishment (PE ).